Native Pollinators (Hymenoptera: Anthophila) in Cotton Grown in the Gulf South, United States - Katherine A. Parys; Isaac L. Esquivel; Karen W. Wright; Terry Griswold; Michael J. Brewer (Agronomy, 2020)
Native bees (Hymenoptera: Anthophila) were sampled using bee bowls in two states to determine biodiversity in commercial cotton fields of the southern United States. In both states, native bee communities found in cotton fields were dominated by generalist pollinators in the genera Agapostemon, Augochloropsis, Halictus, and Lasioglossum (Hymenoptera: Halictidae), and Melissodes (Hymenoptera: Apidae). Melissodes tepaneca (Cresson) was the most abundant species found in cotton fields in both states. Some species collected are known specialists on other plant taxa, suggesting they may be tourist species. Here we provide a baseline species list of native bees found in cotton. Ordination indicated separation between the communities found in the two states when pooled by genus, but these differences were not significant. While cotton is grown in highly managed and disturbed landscapes, our data suggest that a community of common generalist native pollinators persists. Many of these species are also found in other cropping systems across North America.